1986
DOI: 10.1080/00140138608968315
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat-stress induced dehydration on mental functions

Abstract: The effect of primary dehydration of various levels (1, 2 and 3% body-weight deficits) on mental functions of different complexities were studied in eight heatacclimatized subjects drawn from tropical regions of India. These subjects were also studied after a bout of exercise in heat under two conditions viz., Hot Dry (45°C DB, 30% rh), and Hot Humid (39°C DB, 60% rh) at 34OC WBGT. No significant change in routine mental work was seen either under dehydration per se of any level or after subsequent exercise un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
2
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 11 publications
3
103
2
3
Order By: Relevance
“…2) and previous findings: using the same paradigm, drinking prevented a decline in episodic memory and focussed attention (13). Yet the present report contrasts with previous reports in that working memory was not disrupted by a loss of 1-2% of body mass (4,(8)(9)(10) and that even a loss of more than 2% has only sometimes (4-8) been found to be disruptive.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…2) and previous findings: using the same paradigm, drinking prevented a decline in episodic memory and focussed attention (13). Yet the present report contrasts with previous reports in that working memory was not disrupted by a loss of 1-2% of body mass (4,(8)(9)(10) and that even a loss of more than 2% has only sometimes (4-8) been found to be disruptive.…”
Section: Discussioncontrasting
confidence: 57%
“…Although there are reports stating that a loss of body mass greater than 2% disrupts working memory (4,5), this finding has not always been replicated (6)(7)(8). Working memory has never been reported to be disrupted by a loss of 1-2% of body mass (4,(8)(9)(10). As such, if the use of moderated mediation can demonstrate that a small difference in hydration can be disruptive under some conditions, the value of this novel statistical approach would be demonstrated.…”
Section: Objectivesmentioning
confidence: 99%
“…Available studies have identified several domains of cognitive function that are affected by dehydration (Sharma et al, 1986;Gopinathan et al, 1988). Gopinathan et al (1988) examined changes in cognitive function in 11 healthy adult subjects under varying degrees of dehydration induced by a combination of water restriction and heat stress.…”
Section: Pathophysiologymentioning
confidence: 99%
“…For instance, dehydration has well established negative effects on cognitive performance (see Edmonds, 2012, for a review). In adults, dehydration to a loss of more than 2% body weight, induced by heat exposure or exercise, results in poor performance on tasks assessing memory and psychomotor performance (Gopinathan, Pichan, & Sharma, 1988;Sharma, Sridharan, Pichan, & Panwar, 1986); although see Secher and Ritz (2012) for a discussion of methodological limitations. Subjective feelings of concentration and alertness are also negatively affected (Armstrong et al, 2012;Shirrefs, Merson, Fraser, & Archer, 2004;Szinnai, Schachinger, Arnaud, Linder, & Keller, 2005).…”
Section: Introductionmentioning
confidence: 99%